Process development for spray drying a value‐added extract from aflatoxin‐contaminated peanut meal. (22nd August 2012) - Oakes, Aaron J.; White, Brittany L.; Lamb, Marshall; Sobolev, Victor; Sanders, Timothy H.; Davis, Jack P.
Summary: Peanut meal, the primary by‐product of commercial oil crushing operations, is an excellent source of protein although aflatoxin contamination often limits applications for this material. Naturally aflatoxin‐contaminated (59 ppb) peanut meal dispersions were adjusted to pH 2.1 or pH 9.1, with or without additional protease and/or a clay absorbent, and the resulting soluble extracts derived from these dispersions were spray dried. Clay addition during processing minimally affected spray‐drying yields, protein powder solubility or antioxidant capacities, whereas these properties were significantly altered by pH and protease treatments. Spray‐dried hydrolysates produced from peanut meal treated with clay contained significantly less aflatoxin than hydrolysates produced without clay; the effects of pH or enzyme on aflatoxin content were minimal. Peanut meal treated with Alcalase, and clay yielded spray‐dried hydrolysates with enhanced antioxidant capacity and increased solubility compared to unhydrolysed controls and had aflatoxin levels below 1 ppb.